Food Diversification of Female Adolescents At Rimau Islands, Sumur Village: Case Study - Sofyan Musyabiq Wijaya; Dian Isti Anggraini; Surarto Sutarto (Universitas Darussalam Gontor, 2023)
Background: The total nutritional needs during adolescence are higher than at any other time in the life cycle. Nutrition and physical growth are integrally related; Optimal nutrition is a condition for achieving optimal growth potential. This creates an increased need for energy and other nutrients. One of the appropriate policies to be implemented in achieving food independence and anticipating the food crisis is food diversification. Food diversification is a process of food diversity or efforts to increase the consumption of various foods with the principle of balanced nutrition. Objective: The purpose of this study was to determine the diversification of protein source food in young women in the Rimau islands of South Lampung Sumur village. Method: This study used a qualitative design (cases study) using in-depth interviews. The study was conducted within 6 months with 4 respondent Results: The results of the study explained that there limitations in obtaining animal protein sources, thus affecting the diversification of protein sources. Protein sources that are often consumed are eggs and tempeh which do not require a refrigerator in food storage while fish catch hail is sold for economic needs, and is rarely consumed alone. Conclusion: The diversity of protein sources and diet influences the nutritional status of young women at Rimau Islands, Sumur Village, South Lampung.